Randomized controlled trial investigating the effectiveness of a multimodal mobile application for the treatment of chronic pain - Cynthia J. Thomson; Hanna Pahl; Luisa V. Giles (Canadian Journal of Pain)
Background Until recently, treatments for chronic pain commonly relied on in-person interventions, and despite more hybrid care options today, capacity for delivery remains challenged. Digital programs focusing on the psychosocial aspects of pain may provide low-barrier alternatives.Aims Through a randomized controlled trial, we investigated the effectiveness of a multimodal mobile application.Methods Participants (n = 198; 82% women, mean age = 46.7 [13.1] years; mean pain duration 13.6 [11.2] years) with nonmalignant chronic pain were randomized to either a 6-week intervention (n = 98) or a wait-listed usual care group (n = 100). The intervention involved regular engagement with a user-guided mobile application (Curable Inc.) informed by the biopsychosocial model of pain that included pain education, meditation, cognitive behavioral therapy, and expressive writing. The co-primary outcomes were pain severity and interference at 6 weeks.Results We observed significant improvements in the intervention group compared to the control group with estimated changes of −0.67 (95% confidence interval [CI] −1.04 to −0.29, P < .001, d = 0.43) and −0.60 (95% CI −1.18 to −0.03, P = .04, d = 0.27) for pain severity and interference, respectively. There were significant improvements across secondary outcomes (Patient-Reported Outcome Measurement Information System pain interference; pain catastrophizing; anxiety, depression; stress). Frequency of app use was correlated with improved pain interference (P < .001) and pain catastrophizing (P = 0.018), and changes from baseline persisted in the intervention group at 12 weeks (P < .05).Conclusions A short-term mobile app intervention resulted in significant improvements across physical and mental health outcomes compared to wait-listed usual care.